2010
DOI: 10.1007/s11307-010-0322-0
|View full text |Cite
|
Sign up to set email alerts
|

Labeling Human Mesenchymal Stem Cells with Fluorescent Contrast Agents: the Biological Impact

Abstract: PurposeThis study aims to determine the effect of human mesenchymal stem cell (hMSC) labeling with the fluorescent dye DiD and the iron oxide nanoparticle ferucarbotran on chondrogenesis.ProcedureshMSCs were labeled with DiD alone or with DiD and ferucarbotran (DiD/ferucarbotran). hMSCs underwent confocal microscopy, optical imaging (OI), and magnetic resonance (MR) imaging. Chondrogenesis was induced by transforming growth factor-b and confirmed by histopathology and glycosaminoglycan (GAG) production. Data o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 16 publications
0
26
0
Order By: Relevance
“…4A). Cell labeling with nanoparticles has been reported to inhibit chondrogenesis in hMSCs (20). Although the SiNP-loaded cells differentiated down the chondrocyte lineage, we noted a reduced staining intensity compared with unloaded controls (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4A). Cell labeling with nanoparticles has been reported to inhibit chondrogenesis in hMSCs (20). Although the SiNP-loaded cells differentiated down the chondrocyte lineage, we noted a reduced staining intensity compared with unloaded controls (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, the toxic potential of cadmium nanoparticles has remained a concern [20]. Boddington et al reported [21] that the iron oxide nanoparticle ferucarbotran may impair MSC differentiation, which hinders their potential use as fluorescence tracers for stem cells. In contrast, the toxicological effects of amorphous silica have been characterized reasonably well, and this form has been found to be less toxic in animal experiments than that of other nanomaterials.…”
Section: Discussionmentioning
confidence: 99%
“…A major challenge in the treatment of cartilage defects due to arthritis is the lack of self-regeneration capacity of the injured cartilage [3, 4] . New therapies based on matrix-associated chondrocyte implants or matrix-associated stem-cell transplants (MASIs) provide a potentially curative therapeutic option [510] .…”
mentioning
confidence: 99%
“…MRI is currently the only noninvasive diagnostic test that can provide high-resolution anatomical and functional information of cartilage defects in vivo [5,1316]. A variety of iron oxide nanoparticle-based stem-cell markers have been previously applied for cell-tracking purposes [15, 1721] .…”
mentioning
confidence: 99%